Characterization of mouse clonogenic megakaryocyte progenitors - Nakorn, Thanyaphong Na (The National Academy of Sciences, 2003)
Although it has been shown that unfractionated bone marrow, hematopoietic stem cells, common myeloid progenitors, and bipotent megakaryocyte/erythrocyte progenitors can give rise to megakaryocyte colonies in culture, monopotent megakaryocyte-committed progenitors (MKP) have never been prospectively isolated from the bone marrow of adult mice. Here, we use a monoclonal antibody to the megakaryocyte-associated surface protein, CD9, to purify MKPs from the c-kit(+)Sca-1(−)IL7Rα(−)Thy1.1(−)Lin(−) fraction of adult C57BL/Ka-Thy1.1 bone marrow. The CD9(+) fraction contained a subset of CD41(+)FcγR(lo)CD34(+)CD38(+) cells that represent ≈0.01% of the total nucleated bone marrow cells. They give rise mainly to colony-forming unit–megakaryocytes and occasionally burst-forming unit–megakaryocytes, with a plating efficiency >60% at the single-cell level. In vivo, MKPs do not have spleen colony-forming activity nor do they contribute to long-term multilineage hematopoiesis; they give rise only to platelets for ≈3 weeks. Common myeloid progenitors and megakaryocyte/erythrocyte progenitors can differentiate into MKPs after 72 h in stromal cultures, indicating that MKPs are downstream of these two progenitors. These isolatable MKPs will be very useful for further studies of megakaryopoiesis as well as the elucidation of their gene expression patterns.